The long and short of GABAergic neurons - Caputi, Antonio; Melzer, Sarah; Michael, Magdalena; Monyer, Hannah (Current opinion in neurobiology, 2013)
GABA (γ-aminobutyric acid) is the primary inhibitory neurotransmitter in the adult brain. Studies on GABAergic cells have focused almost exclusively on local interneurons neglecting those inhibitory neurons projecting to different brain areas, the ‘long-range GABAergic cells’. This review focuses on some common features and peculiarities of ‘corticofugal’ and ‘corticopetal’ GABAergic cells. Similarly to their local counterpart, long-range GABAergic cells show immunohistochemical diversity and contact locally both excitatory and inhibitory cells. Distally, long-range GABAergic cells often target other inhibitory neurons. This feature endows them with the ability to control remote target areas via disinhibition. On the basis of few functional studies that investigated their participation in synchronous network activity, we propose that long-range GABAergic neurons play a critical role in the temporal coordination of neuronal activity in distant brain areas.